Prospective Evaluation of Pharmacogenomics and Metabolite Measurements upon Azathioprine Therapy in Inflammatory Bowel Disease: An Observational Study. Issue 15 (April 2016) - Fangbin, Zhang; Xiang, Gao; Liang, Ding; Hui, Liu; Xueding, Wang; Baili, Chen; Huichang, Bi; Yinglian, Xiao; Peng, Cheng; Lizi, Zhao; Yanjun, Chu; Feng, Xu; et al.
Abstract : Abstract: Up to approximately 40% to 50% of patients discontinue thiopurine therapy during the course of inflammatory bowel disease (IBD). We investigated the role of the metabolite thiopurine in IBD treatment. This was a prospective study. IBD patients receiving azathioprine (AZA) were prospectively included. Thiopurine methyltransferase (TPMT) genotypes were examined before therapy, and thiopurine metabolite levels were examined at weeks 2, 4, 8, 12, 24, and 48. In total, 132 patients were included. The frequency of leucopenia increased at 6-thioguanine nucleotide (6-TGN) levels ≥420 pmol/8 × 10 8 RBC (odds ratio [OR] = 7.9; 95% confidence interval (95%CI): 3.5–18.0; P < 0.001) and increased more during the initial 12 weeks of thiopurine therapy (OR = 16.0; 95%CI: 5.7–44.9; P < 0.001). The patients with 6-TGN levels ≥420 pmol/8 × 10 8 RBC at weeks 4, 8, and 12 had an increased likelihood of leucopenia. Clinical response increased at 6-TGN levels ≥225 pmol/8 × 10 8 RBC (OR = 13.5; 95% CI: 3.7–48.9; P < 0.001) in Crohn disease (CD) patients. The CD patients with 6-TGN levels ≥225 pmol/8 × 10 8 RBC at weeks 8, 12, and 24 had an increased likelihood of successful clinical response. TPMT∗3C had a specificity of 100%, but a sensitivity of 8% for predicting leucopenia. A 6-TGN level between 225 and 420 pmol/8 × 10 8 RBC could be a therapeutic window in patients receiving AZA therapy, and it could likely predict leucopenia in the initial 12 weeks of AZA therapy and a reasonable chance of successful clinical response in CD patients. The value of TPMT genotyping before thiopurine therapy is limited in Chinese patients with IBD, considering the low sensitivity of predicting leucopenia.